Exploring the river-based tourism product for Muar River: a tourism opportunity spectrum (TOS) approach - Abd Rahman, Nur Hidayah; Abas, Siti Aisah (IOP Publishing Ltd, 2020)
River-based tourism product development is regarded as one of the critical segments that focus on proper physical, social, and economic expansion. To date, the lack of depth and concern is tapped into this market by either scholars or stakeholders accordingly. Currently, a part of the local plan for Muar development is envisioned towards developing and promoting the tourism industry. However, the primary challenge of river-based tourism is maximising the usage and livability of its waters and natural resources. Therefore, this research aimed to explore the suitable tourism product for river-based tourism, with the most significant market potential in the context of the Muar River through an assessment of the Tourism Opportunity Spectrum (TOS). The TOS approach is the methodology suitable as an assessment tool for tourism planning and management towards sustainability. The instrument was adopted from previous studies and executed through site inspection and familiarisation trips, namely observation and resources inventory. The main finding of this study was the zonation of five main areas, which contributed to the characterisation of different tourism products along Muar River, and the five scopes of TOS assessment. The recommendations will primarily support the enhancement of river-based tourism development and assist the stakeholders in achieving the visions and missions of Muar’s local plan.